Da’wah and Universal Goodness Campaign Towards a “Golden” Indonesia 2045: Dakwah dan Kampanye Kebaikan Universal Menuju Indonesia Emas 2045 - Viskhurti, Roland; Ghulam, Zainil (Institut Agama Islam Syarifuddin Lumajang, 2026)
This paper discusses the role of religious communities in Indonesia in optimizing social media,specifically the use of digital public spaces to campaign for universal good. It is hoped that, as weapproach the Golden Indonesia 2045, religious communities in Indonesia can become thebuilding blocks of a noble foundation for reason. Today's society is already so familiar withinternet-based social media and its various platforms. All religions in Indonesia—Islam;Christianity; Catholicism; Buddhism; Hinduism; Confucianism; and other faiths—share acommon human spirit. The massive dissemination of moral, legal, and religious messages, carriedout in a unified manner across each social media channel, can act as a barrier to negativecontent, hoaxes, and hate speech, whether acknowledged or not, that has recently floodedIndonesia's digital world. The theoretical analysis is conducted using several theories andconcepts, namely, Gary R. Bunt's cyber-Islamic environments; Michel Foucault's discourse andideology; Jürgen Habermas's public sphere; and Manuel Castells's network society. This studydemonstrates the urgency of utilizing social media within religious communities to contribute topreparing the best generation and a society that is optimistic about responding to the challengesof the times. The crucial role of religious communities needs to be optimally utilized through theimplementation of concrete programs to welcome Indonesia Emas 2045.